Electron guns for technological linear accelerators - Beloglasov, V.I.; Biller, E.Z.; Vishnýakov, V.A.; Dovbush, L.S.; Zhiglo, V.F.; Zavada, L.M.; Zakutin, V.V.; Kosoy, A.I.; Kushnir, V.A.; Mitrochenko, V.V.; Mýakushko, L.K.; Reshetnýak, N.G.; et al. (Вопросы атомной науки и техники, 1999)
The modern technologies based on linear electron accelerator require intensive beams with small particle losses during acceleration. The beam quality at an accelerator exit is mainly determined by an injector and, in particular, by electron gun. In technological accelerators with a high beam intensity the vacuum accidents are over of danger that can cause the cathode poisoning. In these conditions electron gun designs which let in an operational cathode replacement are preferable. Such an approach was selected for providing the technological accelerators created and developed at the R&D "Accelerator" NSC KIPT with electron guns. The calculations of gun optics and beam characteristics have been carried out both analytically and numerically with using the «EGUN» code [1]. Results of development of three guns are below. The hexaboride lanthanum (LaB6), dispensive tungsten emitter impregnated with barium aluminate and covered by an Os-Ir-Al film, was used as cathodes. The gun tests were conducted at special test installations.